Expressing the Effective Components in Knowledge Network of Research Institute of Petroleum Industry (RIPI) - Zohreh Qolamhosienzadeh; Nosrat Riyahi nia; Mohammad Hassanzaheh; Hmiadreza Arasteh (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2017)
Purpose: The aim of this study is to identify the effective factors in the knowledge Network of research institute of Petroleum Industry. Methodology: This research is applied that done by qualitative method. The study population consisted of 9 members of managers and experts of Research Institute of Petroleum Industry. Purposive sampling method was used For the sampling in this study. To collect the data of dimensions and components related to knowledge network was used semi-structured interviews and content analysis. Findings: By studying the electronic and print resources, identified the 6 effective factors on the knowledge network (strategic, structural, environmental, culture of knowledge sharing, content of knowledge network and infrastructure) and then based on qualitative analysis influencing factors on each of the dimensions were identified. Results: results showed that multidimensional nature of the knowledge network in the Research Instituted of Petroleum Industry according to the interviewees mental patterns linked together and the joint effort, has led to the successful management of knowledge in the institute. Keywords: Knowledge, Knowledge Network, research institute of Petroleum Industry